Newspaper Content Analysis of 2012-2015 Ombaste Ethnic Conflict in Nasarawa State: A Framing Theory Perspective - Sabiu Garba; Aondover Eric Msughter (Budapest International Research and Critics University, 2023)
This study examined the newspaper coverage of the Ombatse crisis that hit Nasarawa State from 2012-2015. The Ombatse was a movement that wanted to resurrect the Eggon culture in a kind of renaissance and ensure a culture of high morality and chastity; laudable as these objectives were, the group suddenly turned dreadful, assuming a more militant posture; attacking and killing enemies real or perceived including security forces in their hundred. The study employed content analysis, which is a quantitative method of data generation. It applied four predetermined frames: actor frame, action frame, reaction frame, and consequence frame. 2112 dailies were censured for the period of four years. Study applied purposive sampling technique in the selection of the Daily Trust and Leadership newspapers where 180 copies of the papers were examined. The found that reaction frame was the predominant slant of the Nigerian newspapers with 61.1% of the news stories as reactions to the Ombatse activities. By implication, the findings revealed vacuity of the Nigerian media in handling a core national issue to which the media itself is a stakeholder. The study recommended that the media must be active participant in addressing, shaping public understanding of social upheaval- because the role of the media during conflict cannot be underestimated. The media should be able to analyse consequences, the possibility of collateral damage on the parties involved, the shadow parties and the by-standers. Nigerian journalists should also be trained and retrained on guide to sensitive-conflict reporting.